Instruments of Artificial Intelligence in Management of High Technology Production - Leizerovich Krichevsky, Mikhail; Vladimirovna Dmitrieva, Svetlana; Anatolevna Martynova, Julia (International Journal of Engineering and Technology, 2018)
The instruments of artificial intelligence (AI) that can be used in management of high technology production and training students are considered. Specific differences and characteristics of high technology production (HTP) that set certain requirements for such production management are specified. Brief information from the AI methods that include artificial neural networks, fuzzy logic, genetic algorithms and their combinations are given. It is indicated that there is a relation between the level of training masters and the requirements of modern productions. The necessity to use techniques and methods of AI when training students to form their competencies, knowledge and skills that comply with the HTP is explained. The techniques of using AI instruments in the educational process focused on the practical importance of the tasks being solved in such disciplines as HR management, risk management, strategic management, etc. are shown.Â Â